2018
DOI: 10.12678/1089-313x.22.3.148
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Skilled Dancers' Focus of Attention on Pirouette Performance

Abstract: Extant attentional focus research has largely examined movement tasks that are outcome-focused (e.g., height of jumps, force production, and number of successful turns) with fewer studies of the movement quality or form of an aesthetic discipline (e.g., dance, gymnastics, and ice-skating). In this study, both movement form and outcomebased measures were used to assess the performance of a pirouette. Thirteen skilled dancers performed pirouettes on a force plate under three trial conditions: control (no focus i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 44 publications
0
3
0
1
Order By: Relevance
“…Thus, equipment-assisted tasks such as batting, dribbling, and juggling, all enable or in some cases initiate movement. Research in classical ballet has provided mixed results with no discernible ( Denardi and Corrêa, 2013 ; Guss-West and Wulf, 2016 ) or negligible effect on performance when using an external focus ( Chua et al, 2018 ). Secondly, many sports-type movements adopted in experimental protocols, involve familiar, action-based hitting, throwing or balancing, i.e., gross motor coordination movements for which participants presumably have a priori , procedural knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, equipment-assisted tasks such as batting, dribbling, and juggling, all enable or in some cases initiate movement. Research in classical ballet has provided mixed results with no discernible ( Denardi and Corrêa, 2013 ; Guss-West and Wulf, 2016 ) or negligible effect on performance when using an external focus ( Chua et al, 2018 ). Secondly, many sports-type movements adopted in experimental protocols, involve familiar, action-based hitting, throwing or balancing, i.e., gross motor coordination movements for which participants presumably have a priori , procedural knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies indicate that some performers adopt an internal focus when not specifically instructed otherwise (Land et al, 2013;Pascua et al, 2015). Further, research in dance has demonstrated that performers' preferred focus, either external or internal, does not always correlate with success (Chua et al, 2018) and that not all dancers employ optimal focus at all times (Guss-West & Wulf, 2016). These studies highlight an opportunity to reimagine training and performance strategies, leveraging evidence-based research and extending application through systematic inquiry.…”
Section: Pedagogical Implicationsmentioning
confidence: 99%
“…While multiple limitations are always present in a first-evidence cross sectional design, more studies will hopefully uncover the longitudinal effects of dance training on general brain plasticity and specific attentional processes. In applied settings, we find a plethora of research highlighting the importance of attention in dance via external and external dance-based foci of attention 58,59 or more spatially relevant proximal-distal attentional information processing. 4,60…”
Section: Attentionmentioning
confidence: 99%